Correlation of hydrogen-bonding propensity and anticancer profile of tetrazole-tethered combretastatin analogues - Jedhe, Ganesh S.; Paul, Debasish; Gonnade, Rajesh G.; Santra, Manas K.; Hamel, Ernest; Tam Luong Nguyen; Sanjayan, Gangadhar J. (Bioorganic & Medicinal Chemistry Letters, 2013)
A series of 1,5-disubstituted tetrazole-tethered combretastatin analogues with extended hydrogen-bond donors at the ortho-positions of the aryl A and B rings were developed and evaluated for their antitubulin and antiproliferative activity. We wanted to test whether intramolecular hydrogen-bonding used as a conformational locking element in these analogues would improve their activity. The correlation of crystal structures with the antitubulin and antiproliferative profiles of the modified analogues suggested that hydrogen-bond-mediated conformational control of the A ring is deleterious to the bioactivity. In contrast, although there was no clear evidence that intramolecular hydrogen bonding to the B ring enhanced activity, we found that increased substitution on the B ring had a positive effect on antitubulin and antiproliferative activity. Among the various analogues synthesized, compounds 5d and 5e, having hydrogen-bonding donor groups at the ortho and meta-positions on the 4-methoxy phenyl B ring, are strong inhibitors of tubulin polymerization and antiproliferative agents having IC50 value in micromolar concentrations. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: Colchicine; Combretastatin; Crystal; Tetrazole; Tubulin

Novel hybrid nocodazole analogues as tubulin polymerization inhibitors and their antiproliferative activity - Kale, Sangram S.; Jedhe, Ganesh S.; Meshram, Sachin N.; Santra, Manas K.; Hamel, Ernest; Sanjayan, Gangadhar J. (Bioorganic & Medicinal Chemistry Letters, 2015)
We describe the design, synthesis and SAR profiling of a series of novel combretastatin-nocodazole conjugates as potential anticancer agents. The thiophene ring in the nocodazole moiety was replaced by a substituted phenyl ring from the combretastatin moiety to design novel hybrid analogues. The hydroxyl group at the ortho position in compounds 2, 3 and 4 was used as the conformationally locking tool by anticipated six-membered hydrogen bonding. The bioactivity profiles of all compounds as tubulin polymerization inhibitors and as antiproliferative agents against the A-549 human lung cancer cell line were investigated Compounds 1 and 4 showed mu M IC50 values in both assays. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Anticancer; Colchicine; Nocodazole; Tubulin binding

Angiotensin II analogs comprised of pro-amb (gamma-turn scaffold) as angiotensin II type 2 (AT(2)) receptor agonists - Jedhe, Ganesh S.; Kotmale, Amol S.; Rajamohanan, Pattuparambil R.; Pasha, Santosh; Sanjayan, Gangadhar J. (Chemical Communications, 2016)
We describe herein the design, synthesis and conformational investigation of Pro-Amb (proline-3-amino-2-methoxybenzoic acid) incorporated Angiotensin II and its truncated analogues. Solution-state NMR and CD studies suggest gamma-turn-like conformation in Pro-Amb analogs in aqueous solution. Furthermore, Pro-Amb analogs have been shown to act as AT(2) receptor agonists.

Residue dependent hydrogen-bonding preferences in orthanilic acid-based short peptide beta-turn motifs - Jedhe, Ganesh S.; Vijayadas, Kuruppanthara N.; Kotmale, Amol S.; Sangtani, Ekta; Shinde, Dinesh R.; Gonnade, Rajesh G.; Rajamohanan, Pattuparambil R.; Sanjayan, Gangadhar J. (RSC Advances, 2016)
This communication describes the competition between native beta-turn (C10) and 2-aminobenzenesulfonic acid (SAnt)( orthanilic acid)-based pseudo beta-turn (C11) in their hybrid peptides. Solid-state crystal structure and solution-state NMR studies revealed that C10 and C11 can be simultaneously observed under appropriate conditions. The variable temperature NMR coefficient data suggest that the isolated C11/C14 hydrogen bond is weaker in comparison with the consecutive C10 and C11 turns.

Design and synthesis of 2-amino-thiophene-tethered ureidopenicillin analogs with potentantibacterial and antitubercular activity - Wagh, Mahendra A.; Baravkar, Sachin B.; Jedhe, Ganesh S.; Borkute, Rachna; Choudhari, Amit S.; Sarkar, Dhiman; Sanjayan, Gangadhar J. (ChemistrySelect, 2018)
Ureidopenicillins are a class of penicillins which are antibiotics active against gram-negative bacteria. Herein, we report the synthesis of 2-aminothiophene-tethered ureidopenicillin analogues and their in vitro antibacterial and antitubercular activity. Intriguingly, unlike the reported ureidopenicillins which are active against gram-negative bacteria, the synthesised 2-aminothiophene-tethered ureidopenicillins were significantly active against Gram-positive bacterial strains and showed moderate inhibition towards gram-negative bacterial strains. Among all the analogs, compound 1b containing 2-aminothiophene moiety with minimum inhibitory concentration (MIC): 0.29, 0.32, > 10, > 10 mg/ml for Staphylococcus aureus, Bacillus subtilis, Escherichia coli and Pseudomonas aeruginosa, respectively, showed better anti-bacterial profile as compared to cephalexin and equipotent to ampicillin and amoxicillin on gram-positive bacterial strains. All the derivatives were also screened for anti-TB activity against mycobacterium tuberculosis H37Ra. Among the series, cycloocta-thiophene-tethered cephalexin analog 3c displayed excellent antitubercular activity with MIC values 0.78 mg/ml. Low cytotoxicity and high selectivity index indicate the efficacy of 3c against mycobacterial infections. The results from present study offer a novel approach to modify the existing drug class of ureidopenicillins to yield antimicrobials with promising utility.